2016
DOI: 10.1373/clinchem.2015.251199
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry–Based Adrenal and Peripheral Venous Steroid Profiling for Subtyping Primary Aldosteronism

Abstract: BACKGROUND:Differentiating patients with primary aldosteronism caused by aldosterone-producing adenomas (APAs) from those with bilateral adrenal hyperplasia (BAH), which is essential for choice of therapeutic intervention, relies on adrenal venous sampling (AVS)-based measurements of aldosterone and cortisol. We assessed the utility of LC-MS/MS-based steroid profiling to stratify patients with primary aldosteronism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(98 citation statements)
references
References 42 publications
6
87
1
2
Order By: Relevance
“…[16][17][18][19][20] An interesting novel approach consists of the measurement of a selected steroid profile by mass spectrometry. 21,22 Nevertheless, additional diagnostic steps will be needed to localize potential APA.…”
Section: Hypertensionmentioning
confidence: 99%
“…[16][17][18][19][20] An interesting novel approach consists of the measurement of a selected steroid profile by mass spectrometry. 21,22 Nevertheless, additional diagnostic steps will be needed to localize potential APA.…”
Section: Hypertensionmentioning
confidence: 99%
“…Even more recently, LC-MS/MS has been used to determine both peripheral and adrenal venous "profiles" of multiple steroids in patients with APA and BAH (394,566). While such analyses are yet to find a place in the routine workup of this condition, already they have yielded important insights, including the apparent superiority of several steroids over cortisol in defining cannulation success during AVS (129), and the much higher levels of both peripheral and adrenal venous 18-oxo-cortisol levels in patients with APAs bearing somatic KCNJ5 mutations compared with APAs without (566). The latter finding is particularly interesting as it supports the concept that somatic KCNJ5 mutations cause (and are probably the predominant basis for) a phenotype that is synonymous with the ANG II-unresponsive form of APA, with excessive production of hybrid steroids now contributing to the list of other similarities (which includes predominant female gender, younger age, larger tumors, more florid PA, lack of aldosterone responsiveness to upright posture and ZF-like morphology, as discussed in section VIF).…”
Section: Figurementioning
confidence: 99%
“…They found that median adrenal/peripheral ratios of 11-deoxycortisol, 17-OHPG, pregnenolone, androstenedione and DHEA were several times higher than those for cortisol. Eisenhofer et al subsequently reported that LC-MS/MS-based steroid profiling during AVS had higher aldosterone lateralization ratios in patients with aldosterone-producing adenoma than immunoassays and suggested that multisteroid panel by LC-MS/MS can identify patients with unilateral disease [26]. Although previous studies of steroid profiling in AVS samples of patients with PA demonstrated higher levels of 11-deoxycortisol and other steroids compared with cortisol [25,26], no comparison was made to directly compare the performance of these markers to that of cortisol in confirming catheter position in the absence of cosyntropin.…”
Section: Discussionmentioning
confidence: 99%
“…Eisenhofer et al subsequently reported that LC-MS/MS-based steroid profiling during AVS had higher aldosterone lateralization ratios in patients with aldosterone-producing adenoma than immunoassays and suggested that multisteroid panel by LC-MS/MS can identify patients with unilateral disease [26]. Although previous studies of steroid profiling in AVS samples of patients with PA demonstrated higher levels of 11-deoxycortisol and other steroids compared with cortisol [25,26], no comparison was made to directly compare the performance of these markers to that of cortisol in confirming catheter position in the absence of cosyntropin. Although cortisol is one of the most abundantly produced adrenal steroids, the lower adrenal to peripheral ratio compared with that of 11-deoxycortisol and other steroids can be explained by the relatively slower clearance of cortisol because most circulating cortisol is bound to globulin [27,28].…”
Section: Discussionmentioning
confidence: 99%